North-South and East-West Relations. Representation and Democratization in Bosnia-Herzegovina - Seixas, Eunice Castro (2011)
Texto da comunicação apresentada a First IPSA-ECPR Joint Conference: Whatever Happened to North-South? S. Paulo, Brasil, 16-19 fevereiro 2011